2007
DOI: 10.1007/s10552-007-9061-1
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to pesticides and risk of hematopoietic cancers: meta-analysis of case–control studies

Abstract: The overall meta-odds ratio suggests that there is a significantly positive association between occupational exposure to pesticides and all hematopoietic cancers as well as NHL. A major limitation of our meta-analysis is the lack of sufficient data about exposure information and other risk factors for hematopoietic cancer (genetic predisposition, ethnic origin, immunodepression...). In addition, data concerning specific subtypes of hematopoietic cancers are often confusing. Thus, future epidemiological studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(102 citation statements)
references
References 83 publications
2
85
1
9
Order By: Relevance
“…When observations were limited to those individuals with more than 10 years of exposure, the risk increased (OR, 1.65; 95% CI, 1.08-1.95). 125 While the meta-analysis supports the hypothesis that pesticides are associated with NHL, they lack sufficient detail about pesticide exposure and other information on risk factors for hematopoietic cancers to identify specific causes. 125 Since the publication of the meta-analysis by Merhi et al, 125 several new population-based studies have been published suggesting that specific pesticides play an important role in NHL etiology.…”
Section: Prostate Cancermentioning
confidence: 94%
See 1 more Smart Citation
“…When observations were limited to those individuals with more than 10 years of exposure, the risk increased (OR, 1.65; 95% CI, 1.08-1.95). 125 While the meta-analysis supports the hypothesis that pesticides are associated with NHL, they lack sufficient detail about pesticide exposure and other information on risk factors for hematopoietic cancers to identify specific causes. 125 Since the publication of the meta-analysis by Merhi et al, 125 several new population-based studies have been published suggesting that specific pesticides play an important role in NHL etiology.…”
Section: Prostate Cancermentioning
confidence: 94%
“…For working on a farm for more than 10 years, the OR was 1.87 (95% CI, 1.15-3.16). 125 None of these studies, however, was able to identify a specific exposure that was associated with multiple myeloma. In the AHS, an excess risk of multiple myeloma was observed in the cohort.…”
mentioning
confidence: 99%
“…Chronic exposure to pesticides indicates the risk of hematopoietic malignancies (Dennis, 1993;Hoshizaki et al, 1969;Loge, 1965;Merhi et al, 2007;Parent-Massin & Thouvenot, 1993;Vial et al, 1996) and might lead to the onset of different pathologies. Possible risk of hematological disorders such as leukemia, multiple myeloma, Hodgkin lymphoma, and nonHodgkin lymphoma were explored (Merhi et al, 2007;Rudant et al, 2007) in agriculture workers, farmers, or employees in chemical industries. A cross-sectional study in cut-flower farmers indicated the hematotoxic effects due to pesticide exposure (Del Prado-Lu, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More recent systematic review studies or case-control studies reported positive association between exposure to pesticides and several cancers including prostate cancer (Van Maele-Fabry and Willems, 2004;Koutros et al, 2010;Doolan G et al, 2014), non-Hodgkin lymphoma (NHL) (Merhi et al, 2007;Balasubramaniam et al, 2013;Yildirim et al, 2013;Schinasi and Leon, 2014), leukemia (Merhi et al, 2007;Van Maele-Fabry et al, 2008), multiple myeloma (Merhi et al, 2007) and lung cancer (Ganesh et al, 2011;Luqman et al, 2014). In the case of esophageal or gastric cancer, no relationship with pesticide usage was reported in recent Turkey study (Yildirim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%